Kewenangan Pemerintah Propinsi Jawa Barat dalam Membuat Peraturan Daerah Provinsi yang Berkaitan dengan Penanaman Modal di Wilayah Propinsi Jawa Barat - Efik Yusdiansyah (Syiar Hukum, 2010)
One of the power of District/City Government is to deal with investment affair, which is governed by Regional Regulation. In fact, such regulation governs from license process to the determination of retribution amount, which is classified as a regional tax. Although this regional revenue aims to improve public services in order to boost investment, it has created unfair competition among the  District/City Governments in an attempt to get investor by ignoring all legitimate interests of other District/City Governments. Based on the above background, this article seeks to examine the function and role of the West-Jawa Province Government in regulating the investment matter. The issues that will be discussed in this article as follows: (1) Whether the West-Java Province Government has the authority to govern the regional regulation relating to investment?; (2) What steps that can be taken by the Province Government to make Law Harmonization in investment arrangement at a regional level?; and (3) Can the District/City Government Regulation, which is considered to be hampering the investment business climate, be revoked by the West-Java Province Government ?